Análisis de las interacciones medicamentosas en un paciente polimedicado con artrosis, diabetes mellitus ii e hipertensión arterial - Velasco Pesantez, Ronny Wilfrido (Machala : Universidad Técnica de Machala, 2021)
Introduction: Pluripathological older adults are characterized by being polymedicated patients, which contributes to the emergence of drug interactions harming the health of these patients further therefore need adequate control of pharmacological and non-pharmacological treatments that prevent drug interactions. Objective: To analyze drug interactions in a polymedicated patient with Osteoarthritis, Type II Diabetes Mellitus and Hypertension. Methods: This work was qualitative of descriptive and deductive type using articles and books of high impact of the last years for the resolution of this clinical case. Results: Interactions were found between drug to drug and alcohol drug of pharmacokinetic and pharmacodynamic character. Conclusion: Drug interactions are frequent and even more in older adults who are found polymedicated these interactions can decrease the therapeutic effect, increase the risk of adverse reactions such as upset stomach, nosebleeds, etc. For this reason a pharmacological and non-pharmacological treatment was implemented to reduce the risk of interactions contributing to the improvement of the patient’s health.
Introducción: Los adultos mayores pluripatológicos se caracterizan por ser pacientes polimedicados, lo que contribuye a la aparición de interacciones medicamentosas perjudicando a un más la salud de estos pacientes por ende necesitan un control adecuando del tratamientos farmacológico y no farmacológico que eviten las interacciones entre fármacos. Objetivo: Analizar las interacciones medicamentosas en un paciente polimedicado con Artrosis, Diabetes Mellitus tipo II e Hipertensión arterial. Método: Este trabajo fue cualitativo de tipo descriptivo y deductivo utilizando artículos y libros de alto impacto de los últimos años para la resolución de este caso clínico. Resultados: Se encontraron interacciones entre fármaco a fármaco y fármaco alcohol de carácter farmacocinético y farmacodinámica. Conclusión: Las interacciones medicamentosas son frecuentes y aún más en adultos mayores que se encuentran polimedicados estas interacciones pueden disminución del efecto terapéutico, aumentar el riesgo de reacciones adversad como malestar estomacal, hemorragias nasales, etc. Por tal motivo se implementó un tratamiento farmacológico y no farmacológico para disminuir el riesgo de interacciones contribuyendo a la mejora de la salud del paciente.
Keywords: POLIMEDICADO; PLURIPATOLOGICO; REACCIONES ADVERSAS; METFORMINA